2020
DOI: 10.3390/nano10102081
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrocatalytic and Gas Transport Characteristics of Pentagonally Structured Star-Shaped Nanocrystallites of Pd-Ag

Abstract: The method of synthesis of bimetallic Pd–Ag pentagonally structured catalyst “nanostar” on the surface of Pd-23%Ag alloy films has been developed. The resulting catalyst was studied as a highly active functional layer for methanol oxidation reaction (MOR) in alkaline media and the intensification of hydrogen transport through the Pd-23%Ag membrane in the processes of hydrogen diffusion purification. A modifying layer with a controlled size, composition and excellent electrocatalytic activity was synthesized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…We used DDW containing δ 2 H = −679‰, produced on a set-up developed at Kuban State University [ 19 , 20 ]. Water that was physiologically complete in terms of mineral components and with a deuterium content of −679‰ was obtained by adding mineral salts to it (mineralization 314–382 mg/L: hydrocarbonates—144–180, sulfates <1, chlorides—60–76, calcium—6, magnesium—3, sodium—50–58, potassium—50–58).…”
Section: Methodsmentioning
confidence: 99%
“…We used DDW containing δ 2 H = −679‰, produced on a set-up developed at Kuban State University [ 19 , 20 ]. Water that was physiologically complete in terms of mineral components and with a deuterium content of −679‰ was obtained by adding mineral salts to it (mineralization 314–382 mg/L: hydrocarbonates—144–180, sulfates <1, chlorides—60–76, calcium—6, magnesium—3, sodium—50–58, potassium—50–58).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it can be concluded that the formation of a classical smooth palladium layer on the niobium membranes surface does not provide the maximum possible permeability of niobium under operating conditions, since it does not remove all surface limitations. In this case, one way to increase hydrogen recovery may be to increase the active surface area of the membrane by applying a modifying nanostructured coating [ 22 , 23 , 24 ]. Such solution can play a positive role in the acceleration of dissociative–associative processes on the surface, significantly increasing the hydrogen permeability [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a different range of pressure of the H 2 -N 2 atmosphere has been considered for their application [27] and low temperature bonding has been proved to give good sealing properties [28]. Moreover, on-site repair was exploited [29], various types of nanostructuring of the surfaces were considered [30,31], and the extraction of H 2 from biomaterials was achieved [32].…”
Section: Introductionmentioning
confidence: 99%